Effect of Herbal Plant Extracts on Inhibition of Pathogenic Bacteria in Nile Tilapia (Orechromis niloticus) - Wattanuruk, Duangduan; Detraksa, Janejira (Journal of Food Health and Bioenvironmental Science, 2023)
Herbal plant extracts could be an alternative treatment tilapia fish for diseases. This research was carried out to evaluate the antimicrobial potential of several plant extracts against fish pathogenic bacteria isolated from diseased or health Nile tilapia. This study selected twenty plant extracts to determine anti-bacterial activity by agar well diffusion method on trypticase soy agar (TSA).Aqueous ethanolic extracts of herbs were tested for activity against three fish pathogenic bacteria, including Aeromonas hydrophila, Streptococcus agalactiae and Edwardsiella ictaluri. Effective herbal plant extracts was selected to investigate the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values against representative bacterial stains by broth dilution method. The results showed that Terminalia chebula, Acacia catechu, Glycyrrhiza glabra, Psidium guajava, Houttuynia cordata, Piper sarmentosum and Garcinia mangostana extracts could inhibit all strains of the test bacteria. However, inhibitory zone effects of A. catechu extracts showed the best activity against A.hydrophila, S.agalactiae and E.ictaluri at 22.66±0.29 mm, 24.33±0.09 mm and 21.33±0.34 mm, respectively when compared with other herb extracts, with the zone of inhibition ranging from 8.33±0.84 to 19.33±0.04 mm Generally, MIC and MBC concentration values of A. catechu extracts that ranged between 6.5 and 12.5 mg/mL of aqueous plant extracts for all pathogens tested. The results suggest that herbal plant extracts showing several biological activities may be potent inhibitors as a natural anti-bacterial in Nile tilapia.The findings suggest that herbal plant extracts could be a potential alternative to fish disease therapy.